Hubungan Jumlah Eosinofil dengan Ukuran Polip Nasal dan Karakteristik Pasien yang Didiagnosis di Sentra Diagnostik PA FK-UNAND Tahun 2017-2019 - Khairunnisa, Salma Yuri; Tofrizal, Tofrizal; Suharti, Netti (Jurnal Ilmu Kesehatan Indonesia, 2021)
Background: Nasal polyps is a soft masses filled with fluid in nasal mucosa. The incidence is not high, but nasal polyps are related with inflammatory process. Factors that can affect nasal polyps are eosinophils, polyp size, age and gender of the patient. Objective: This study aims to discuss the association between eosinophils with polyp size, age and gender of polyp patient. Methods: The type of this study was an analytic using a cross sectional approach. This research took place from February- October 2020 in the Pathology Anatomy Diagnostic Central of Faculty of Medicine, Andalas University with 19 total sample and this study used total sampling technique. Results: The results based on bivariate analysis of Chi-Square test between amount of eosinophils with polyp size, age and gender of polyps patients have p values (p = 0, 036), (p = 0.264), (p = 1, 00). Conclusion: There is a significant relationship between eosinophils and polyp size. There is no significant relationship between eosinophils with age and gender of patients with nasal polyps in the Pathology Anatomy Diagnostic Central of Faculty of Medicine, Andalas University in 2017- 2019.